Pengaruh Perencanaan dan Pengorganisasian Terhadap Kinerja Guru - Ali Mukti Tanjung; Budi Siregar; Ahmad Karim; Ari Kartiko; Dian Saputra (Al-Mada: Jurnal Agama, Sosial, dan Budaya, 2022)
This study aims to determine how much influence planning has on teacher performance in public elementary schools throughout Pagar Merbau District, Deli Serdang Regency. Knowing how much influencers teachers’ performance in SD Negeri in Pagar Merbau District, Deli Serdang Regency. Knowing how much influence planning and organization have on teacher performance in Public Elementary Schools in Pagar Merbau District, Deli Serdang Regency. This type of research is categorized as field research, namely research carried out in the arena or field where symptoms occur. The results of this study were planning on teacher performance of 0.245 or 24.5%. These results indicate that the planning variable has a low influence on teacher performance in public elementary schools throughout Pagar Merbau District Deli Serdang Regency by 0.245 or 24.5%. Organization of 0.712 or 71.2%. These results indicate that the organizing variable has a strong influence on teacher performance of 0.712 or 71.2%. Planning and organizing on teacher performance is 0.746 or 74.6%, which means that we can conclude from the third hypothesis that it is proven that there is a strong influence between the two independent variables on the dependent variable.